Ecarin Clotting Time: a Predictive Coagulation Assay for the Antithrombotic Activity of Argatroban in the Rat - Berry, Christopher N.; Lunven, Catherine; Girardot, Christine; Lechaire, Irène; Girard, Denise; Charles, Marie-Christine; Ferrari, Patrice; O’Brien, Donogh P. (Thrombosis and Haemostasis, 1998)
We studied the use of the Ecarin Clotting Time (ECT) as a predictive assay of the antithrombotic effects of argatroban in a new tissue factor-dependent model of venous thrombosis and a model of arterial thrombosis in the rat. Heparin was used as a reference anticoagulant.Infusions of argatroban dose-dependently increased the ECT across the range of doses required for antithrombotic activity in models of venous and arterial thrombosis (1.25-40 μg/kg/min). The TT was only useful as a marker in the case of venous thrombosis, since, in the arterial thrombosis model, the clotting times were >200 s in the majority of animals receiving antithrombotic doses. The aPTT is not sufficiently sensitive to be predictive of an antithrombotic effect in the venous model, and shows only modest increases in the arterial thrombosis model. Heparin did not significantly increase the ECT at antithrombotic doses in the venous thrombosis model, and only increased the ECT by 53% at 40 μg/kg/min in the arterial model, despite a marked antithrombotic effect. Both the TT and aPTT were dose-dependently increased by heparin at doses active in the venous model, whereas both parameters were >200 s at doses active in the arterial thrombosis model.Thus, the ECT provides a predictive marker for the antithrombotic activity of argatroban in both venous and arterial thrombosis, at least in the rat.